Basic structure doctrine and its application in Malaysia: with reference to decided cases - Ali Mohamed, Ashgar Ali (CLJ Publication, 2020)
What is emphasised is that the judiciary is empowered to strike down an amendment to the Constitution or any enacted laws which conflicts with or seeks to alter the basic structure of the Constitutio